(untitled) (Jurnal Bahasa Lingua Scientia, 2024)
Teaching speaking is intrinsically complicated but it is quite challenging at once. Pragmatic competence, an essential element of speaking competence, refers to the ability to use appropriately selected forms of language to express and to interpret the intended speaker’s meanings in various contexts. Despite its vital role in fostering social harmony within everyday communication, developing such a competence seems ’easier said than done’. As pessimistically voiced by some EFL speaking teachers and several empirical studies, this ability does not seem well developed among EFL students of all education levels in Indonesia. Hence, English speaking teachers in this country should pull out all the stops to find a potentially effective teaching strategy in this issue. This article proposes a prescribed roleplay, enhanced by the utilization of social media applications, i.e. YouTube or Instagram, for teaching a speech act. The utilization of social media platforms potentially generates students’ learning motivation since it enables them to have a one-click access to authentic speaking learning resources and to journal students’ progress in conversational practices. This prescribed roleplay comprises twofold stages, i.e. (i) to activate the students’ pragmatic awareness and (ii) to execute a step-by-step instructional activities; Hopefully, such a teaching practice will inspire our dedicated ELT speaking teachers aiming at developing pragmatic competence within the students’ speaking command.